PENGARUH KUALITAS PELAYANAN DAN POTONGAN HARGA TERHADAP MINAT BELI KONSUMEN PADA TOKO BUKU ZANAFA PEKANBARU - Roza, Lia; Sutrisna, Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Service quality can be determined by comparing consumers' perceptions of the services they actually receive / get with the services they actually expect / want for the service attributes of a company. Discount is a discount given by the seller to the buyer as a tribute to certain activities of the buyer who are pleasing to the seller. Consumer buying interest can be influenced by product quality, price, location and service quality. So in this case, the company must be able to know what is the desire of the consumers themselves in order to continue to have an interest in a product, both goods and services.            This research was conducted at the Zanafa Pekanbaru Bookstore located on Jalan HR. Subrantas Complex MTC / Giant Blok A 39-41 Pekanbaru. The problem in this study is that it does not reach 80% of the desired sales target and the number of consumers in the Zanafa Bookstore has decreased in 2017. This is thought to be influenced by consumer buying interest.            The purpose of this study was to determine the effect of service quality and price discounts on the buying interest of Zanafa Bookstore consumers. In this research the method used is quantitative descriptive with SPSS program. The sample of this study was taken as many as 100 respondents from a total population of 57,128 which was calculated using the Slovin formula. The data collection method uses a questionnaire. Hypothesis testing uses simple and multiple linear regression analysis methods.            The results showed that service quality and price cuts significantly influence buying interest in the Pekanbaru Zanafa Bookstore. Keywords: Service Quality, Price Discount, And Consumer Buying Interest